Comparison Of Inquiry And Problem Solving Approaches Towards Improving Students' Mathematical Reasoning Ability And Self Confidence High School Students - Hutasuhut, Addiestya Rosa; Surya, Edy; Arnita, Arnita (UIN Sunan Gunung Djati Bandung, 2024)
The study aims to identify differences between improved mathematical reasoning skills of students taught with inquiry approaches and mathematics problem solving education approaches; to determine differences in improved self-confidence of teaching students with inquisition approaches, and in mathematically solving educational approaches. This research is categorized into quasy experimental research. This research is being carried out at one of the Higher Secondary Schools in Labuhan Batu regency in the academic year 2023/2024, with the timetable for the conduct of research coordinated according to the school's activities. The subject of this study is a total of 72 high school X-grade students. The results of this survey show that; there is a difference between improved mathematical reasoning skills of students with inquiry approaches and problem solving approaches; there are differences in improved self-confidence students with Inquiry and Problem Solving Approaches; There is a distinction between inquery and problem-solving mathematics education approaches to enhanced mathematic reasoning ability and self confidence